2013
DOI: 10.1111/fwb.12104
|View full text |Cite
|
Sign up to set email alerts
|

Multiple environmental stressors confine the ecological niche of the rotifer Cephalodella acidophila

Abstract: The planktonic food web in extremely acidic mining lakes is restricted to a few species that are either acidophilic or acidotolerant. Common metazoans inhabiting acidic mining lakes with a pH below 3 include rotifers in the genera Cephalodella and Elosa.The life history response of Cephalodella acidophila to three environmental key factors, pH (2, 3.5, 5.0 and 7.0), temperature (10, 17.5 and 25 °C) and food concentration (10 000, 35 000 and 50 000 algal cells per mL), was investigated in a full factorial desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…As cyclically parthenogenetic zooplankters evolve rapidly (Fussmann 2011;Declerck et al 2015), it is plausible to conjecture adaptation of diapause stage production patterns under high heavy metal fluctuations. High heavy metal concentrations are known to affect the rotifer community (Cecchine and Snell 1999;Weisse et al 2013). Additionally, the diapause pattern observed in different organisms as response to arsenic might be a general response to stressors (Aruda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As cyclically parthenogenetic zooplankters evolve rapidly (Fussmann 2011;Declerck et al 2015), it is plausible to conjecture adaptation of diapause stage production patterns under high heavy metal fluctuations. High heavy metal concentrations are known to affect the rotifer community (Cecchine and Snell 1999;Weisse et al 2013). Additionally, the diapause pattern observed in different organisms as response to arsenic might be a general response to stressors (Aruda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, mining operations are intense in the region, mainly focused on copper; these contribute to presence of the metals in the waters (Díaz-Palma et al 2012). Not surprisingly, biodiversity in lakes near mining areas is greatly reduced, and zooplankton community structure shows strong particularities (Weisse et al 2011(Weisse et al , 2013. In past decades, mining and the concomitant arsenic concentration in the environment have been associated with severe damage to human health, especially in rural populations (Naujokas et al 2013;Yañez et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent experimental evidence with freshwater ciliates, flagellates, and microeukaryotes revealed that the realized pH niche may be confined to a small range, relative to the fundamental pH assessed in the laboratory under optimized conditions. This is because there is a significant interaction of pH with food and temperature (Moser and Weisse 2011;Weisse 2006;Weisse et al 2002Weisse et al , 2013a. Interaction of pH with food quality was obvious for both ciliate species of this study; the pH niche was narrower and, in the case of G. bromelicola, restricted to the pH range typical of bromeliad reservoirs if bacteria were the only food ( Fig.…”
Section: Why Are Both Ciliates Restricted To Tank Bromeliads?mentioning
confidence: 74%
“…Lakes at different pH naturally host different communities, with more acidic lakes generally hosting fewer species (Bielanska-Granier, 2001;Weisse et al, 2013). Yet, rotifer communities are known to be present in water bodies with different pH.…”
Section: Effects Of Ph and Copper On Rotifers At The Community Levelmentioning
confidence: 99%